Application of Computer-Based Simulation Teaching Combined with PBL in Colorectal Tumor Hemorrhage - Yanling Zhang; Jinyan Hu; Lingling Li; Yunpeng Zhao (Emergency Medicine International)
Objective. This paper aims to explore the use of computer-based simulation teaching combined with PBL in colorectal tumor bleeding. Methods. The outpatient department organized 21 nursing staffs to conduct computer simulation combined with PBL teaching, compared emergency theory and skill scores, and investigated the recognition of computer simulation teaching combined with PBL. Results. The scores of theoretical knowledge examination before training were (84.31 ± 6.39) and (92.59 ± 2.93) after training; the scores of treatment skills examination were (85.69 ± 6.15) and (95.43 ± 2.88) after training; the scores of comprehensive treatment skills before training were (76.6 ± 6.31) and (91.43 ± 2.3) after training. The results of the questionnaires showed that the nurses were more agreeable to the new teaching methods and were able to complete the tasks in strict accordance with the requirements, ultimately achieving a level of satisfaction with their progress. Conclusion. Computer simulation teaching combined with PBL can deepen general practitioners’ understanding of knowledge, improve practical ability, and provide a clinical basis for improving patient resuscitation in specialized oncology hospitals.